TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PERMAINAN JUDI JACKPOT (Studi Kasus Putusan Nomor 45/Pid.B/2017/PN.MDN) - Mesias J.P Sagala (Universitas Islam Sumatera Utara, 2019)
Indonesia is a legal state where all aspects of people's lives in nation have norms that must be obeyed. These norms aim to prevent criminal acts. Criminal act is an act that is prohibited by the rule of law, and the prohibition is accompanied by threats and sanctions in the form of criminal violations of such prohibitions, such as gambling which is an act of betting deliberately carried out to benefit from a match, game or event that is uncertain about the result. For example, jackpot gambling games that use machine technology are played by inserting coins in the form of chips of money that have been exchanged for a certain value of money and inserted into the machine and then pulled by the player, then waiting for the combination image to come out simultaneously on the jackpot machine and if the image is the same, then it is considered to win a different cash prize depending on the interest or image that the player gets. This game is a chancy game that can be said as gambling because of bets between players. Keyword: Criminal Act, Gambling, Jackpot Gampling